Evaluation of RAPNO criteria in medulloblastoma and other leptomeningeal seeding tumors using MRI and clinical data. Issue 10 (26th June 2020) - Peng, Jian; Zhou, Hao; Tang, Oliver; Chang, Ken; Wang, Panpan; Zeng, Xiaowei; Shen, Qin; Wu, Jing; Xiao, Yanhe; Patel, Sohil H; Hu, Chongyu; Jin, Ke; et al.
Abstract: Background: Although the Response Assessment in Pediatric Neuro-Oncology (RAPNO) working group has made recommendations for response assessment in patients with medulloblastoma (MBL) and leptomeningeal seeding tumors, these criteria have yet to be evaluated. Methods: We examined MR imaging and clinical data in a multicenter retrospective cohort of 269 patients with MBL diagnoses, high grade glioma, embryonal tumor, germ cell tumor, or choroid plexus papilloma. Interobserver agreement, objective response (OR) rates, and progression-free survival (PFS) were calculated. Landmark analyses were performed for OR and progression status at 0.5, 1.0, and 1.5 years after treatment initiation. Cox proportional hazards models were used to determine the associations between OR and progression with overall survival (OS). Subgroup analyses based on tumor subgroup and treatment modality were performed. Results: The median follow-up time was 4.0 years. In all patients, the OR rate was .0.565 (95% CI: 0.505–0.625) by RAPNO. The interobserver agreement of OR determination between 2 raters (a neuroradiologist and a neuro-oncologist) for the RAPNO criteria in all patients was 83.8% ( k statistic = 0.815; P  < 0.001). At 0.5-, 1.0-, and 1.5-year landmarks, both OR status and PFS determined by RAPNO were predictive of OS (hazard ratios [HRs] for 1-year landmark: OR HR = 0.079, P  < 0.001; PFS HR = 10.192, P  < 0.001). In subgroup analysis, OR status and PFS were predictive of OS for all tumor subtypes and treatment modalities. Conclusion: RAPNO criteria showed excellent consistency in the treatment response evaluation of MBL and other leptomeningeal seeding tumors. OR and PFS determined by RAPNO criteria correlated with OS.